2019
DOI: 10.1038/s41467-019-10461-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analysis of environmental and genetic influences on cord blood DNA methylation in new-borns

Abstract: Epigenetic processes, including DNA methylation (DNAm), are among the mechanisms allowing integration of genetic and environmental factors to shape cellular function. While many studies have investigated either environmental or genetic contributions to DNAm, few have assessed their integrated effects. Here we examine the relative contributions of prenatal environmental factors and genotype on DNA methylation in neonatal blood at variably methylated regions (VMRs) in 4 independent cohorts (overall n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 79 publications
5
69
0
Order By: Relevance
“…Genetic variants in FKBP5 influence local chromatin structure and mC levels, which correlate with measures of brain structure (hippocampal volume) and PTSD symptoms in individuals exposed to childhood trauma (27). Similarly, Teh et al (65) showed that the interaction of local genetic variants and aspects of the prenatal environment best explained variation in mC at 75% of genomic regions in human umbilical cord samples, a finding that is consistent with recent findings in neonatal blood (66). Such allele-specific epigenetic effects may provide a biological mechanism to explain gene-byenvironment interactions (27).…”
Section: Adenine Methylationsupporting
confidence: 62%
“…Genetic variants in FKBP5 influence local chromatin structure and mC levels, which correlate with measures of brain structure (hippocampal volume) and PTSD symptoms in individuals exposed to childhood trauma (27). Similarly, Teh et al (65) showed that the interaction of local genetic variants and aspects of the prenatal environment best explained variation in mC at 75% of genomic regions in human umbilical cord samples, a finding that is consistent with recent findings in neonatal blood (66). Such allele-specific epigenetic effects may provide a biological mechanism to explain gene-byenvironment interactions (27).…”
Section: Adenine Methylationsupporting
confidence: 62%
“…These results suggest the need for studies that integrate analyses of both DNA sequence and DNA methylation. The findings of Teh et al (34) are bolstered by Czamara et al (35), who investigated the relative contributions of prenatal environmental factors and SNPs on DNA methylation at variably methylated regions in neonatal blood, in four independent cohorts (n = 2,365).…”
Section: Gene-environment Interplaymentioning
confidence: 96%
“…Notably, both models (G+E and GxE) were enriched for DMRs associated with GWAS of psychiatric disease, including MDD. 68 In another mechanistic study of GxE interactions driving epigenetic modifications, Klengel et al 69 identified an interaction between a variant (rs1360780) located in an enhancer region in FK506 binding protein 5 gene (FKBP5) and childhood trauma on DNA methylation of FKBP5 in peripheral blood cells. FKBP5 is an important regulator of the HPA axis and is involved in a negative feedback loop to terminate the stress response.…”
Section: Gene X Environment Mechanisms In Depressionmentioning
confidence: 99%